Histidine biosynthesis plays a crucial role in metal homeostasis and virulence of Aspergillus fumigatus. Issue 4 (18th May 2016) - Dietl, Anna-Maria; Amich, Jorge; Leal, Sixto; Beckmann, Nicola; Binder, Ulrike; Beilhack, Andreas; Pearlman, Eric; Haas, Hubertus
Abstract: Aspergillus fumigatus is the most prevalent airborne fungal pathogen causing invasive fungal infections in immunosuppressed individuals. The histidine biosynthetic pathway is found in bacteria, archaebacteria, lower eukaryotes, and plants, but is absent in mammals. Here we demonstrate that deletion of the gene encoding imidazoleglycerol-phosphate dehydratase (HisB) in A. fumigatus causes (i) histidine auxotrophy, (ii) decreased resistance to both starvation and excess of various heavy metals, including iron, copper and zinc, which play a pivotal role in antimicrobial host defense, (iii) attenuation of pathogenicity in 4 virulence models: murine pulmonary infection, murine systemic infection, murine corneal infection, and wax moth larvae. In agreement with the in vivo importance of histidine biosynthesis, the HisB inhibitor 3-amino-1, 2, 4-triazole reduced the virulence of the A. fumigatus wild type and histidine supplementation partially rescued virulence of the histidine-auxotrophic mutant in the wax moth model. Taken together, this study reveals limited histidine availability in diverse A. fumigatus host niches, a crucial role for histidine in metal homeostasis, and the histidine biosynthetic pathway as being an attractive target for development of novel antifungal therapy approaches.